Pleasant Pain Relief and Inhibitory Conditioned Pain Modulation: A Psychophysical Study - Nathalie Bitar; Serge Marchand; Stéphane Potvin (Pain Research and Management)
Background. Inhibitory conditioned pain modulation (ICPM) is one of the principal endogenous pain inhibition mechanisms and is triggered by strong nociceptive stimuli. Recently, it has been shown that feelings of pleasantness are experienced after the interruption of noxious stimuli. Given that pleasant stimuli have analgesic effects, it is therefore possible that the ICPM effect is explained by the confounding effect of pleasant pain relief. The current study sought to verify this assumption. Methods. Twenty-seven healthy volunteers were recruited. Thermal pain thresholds were measured using a Peltier thermode. ICPM was then measured by administering a tonic thermal stimulus before and after a cold-pressor test (CPT). Following the readministration of the CPT, pleasant pain relief was measured for 4 minutes. According to the opponent process theory, pleasant relief should be elicited following the interruption of a noxious stimulus. Results. The interruption of the CPT induced a mean and peak pleasant pain relief of almost 40% and 70%, respectively. Pleasant pain relief did not correlate with ICPM amplitude but was positively correlated with pain level during the CPT. Finally, a negative correlation was observed between pleasant pain relief and anxiety. Discussion. Results show that the cessation of a strong nociceptive stimulus elicits potent pleasant pain relief. The lack of correlation between ICPM and pleasant pain relief suggests that the ICPM effect, as measured by sequential paradigms, is unlikely to be fully explained by a pleasant pain relief phenomenon.